A Review of Microbiology: An Evolving Science, Second EditionReview of: Microbiology: An Evolving Science, 2nd ed.; Joan L Slonczweski and John W. Foster; (2011). W.W. Norton & Company, New York NY. 1096 pages. ISBN: 978-0-393-93447-2. - Barbara May (American Society for Microbiology, 2011)
Review of: Microbiology: An Evolving Science, 2nd ed.; Joan L Slonczweski and John W. Foster; (2011). W.W. Norton & Company, New York NY. 1096 pages. ISBN: 978-0-393-93447-2.